Hydrogen Production from Low-Grade Agricultural Waste: Integrated Drying, Gasification, and Chemical Looping - Kyohsuke Miyahira (AIDIC Servizi S.r.l., 2021)
Chemical looping hydrogen production (CLH2) is a new technology used to produce H2 from fuel while separating CO2 simultaneously. Rice husk is considered as a promising energy source in the future because of its high energy potential and carbon neutral characteristics, although currently it is not being used effectively. This research aims to build an integrated conversion system of rice husks to H2 with high energy efficiency. The developed system mainly consists of superheated steam drying, steam gasification, syngas chemical looping, and Haber-Bosch process. To enhance the efficiency, exergy recovery and process integration technologies are adopted. Fe2O3 and Al2O3 are used as oxygen carrier and heat carrier for CLH2. The energy efficiency is evaluated using Aspen Plus. The effect of chemical looping temperature, and the effect of recycle to feed stream ratio for NH3 synthesis were selected for the parameters and evaluated. The highest NH3 efficiency achieved through the simulation was 5.77 % and the power efficiency was 1.96 %.